Pharmaceutical Regulatory Environment Challenges and Opportunities in the Gulf Region - Al-Essa, Reem K.; Al-Rubaie, Mohammed; Walker, Stuart; Salek, Sam (Springer International Publishing : Imprint: Adis, 2015)
The Middle East represents the next growth market for the global biopharmaceutical industry but to date there has been limited information about the regulatory review processes employed in these countries. A thorough examination of the strategies currently being implemented by the Gulf States is considered critical to the future regulatory environment in this region. This book compares national and centralised procedure practices and key performance metrics, including current approval times, review practices and pharmacovigilance standards, in the seven Gulf States. Opportunities for an improved regulatory system are identified, which, if fully implemented, could have a significant impact on patients' access to new medicines. Pharmaceutical Regulatory Environment: Challenges & Opportunities in the Gulf Region is a must read for those interested in pharmaceutical regulation in the Gulf region.